Feasibility and safety of sequential research‐related tumor core biopsies in clinical trials1. Issue 7 (20th December 2012) - Lee, Jung‐min; Hays, John L.; Noonan, Anne M.; Squires, Jennifer; Minasian, Lori; Annunziata, Christina; Wood, Bradford J.; Yu, Minshu; Calvo, Katherine R.; Houston, Nicole; Azad, Nilofer; Kohn, Elise C.
Abstract BACKGROUND: There has been increasing interest in serial research biopsies in studies of targeted therapies. Definition of patient characteristics and optimal target tissue for safe research tumor biopsy in the era of antiangiogenic and targeted agents is needed. METHODS: This institutional review board‐approved, retrospective study included chart and interventional radiology case review from 6 phase 1/2 studies at the National Cancer Institute. RESULTS: One hundred forty‐two of 150 protocol patients who were approached gave consent for research biopsies. Patients' median age was 56 years (range, 27‐78 years), their median body mass index was 25.8 kg/m2 (range, 14.4‐46.2 kg/m2), they had an Eastern Cooperative Oncology Group performance status of 0 or 1, and they had normal end‐organ function. Baseline biopsies were collected from 138 of 142 patients (97%), and paired specimens were collected from 96 (70%). Most patients had metastatic gynecologic cancers (85%), and 78% had target disease below the diaphragm with a median size of 2.7 cm (range, 1‐14.5 cm). Protocol therapies included kinase inhibitors (35%), angiogenesis inhibitors (54%), and olaparib/carboplatin (11%); therapy was not interrupted for biopsies. All adverse events were uncomplicated and were observed in 4 patients (liver subcapsular hematoma in 1 patient, vasovagal syncope in 2 patients, and pneumothorax in 1 patient). The complication rate in obese patients was similar to that in nonobese patients (3 of 108 patients vs 1 of 34 patients, respectively). Sixty‐seven patients (48%) were receiving bevacizumab at the time of subsequent biopsies. The complication rate was not different between patients who were and were not receiving bevacizumab (3 of 67 patients vs 1 of 71 patients, respectively). Ninety‐five percent of biopsies yielded useable material. CONCLUSIONS: Serial percutaneous core‐needle biopsies can be obtained safely and yield material applicable for multiple translational applications. Obesity and/or concomitant antiangiogenic therapy and depth of disease did not increase the risk or preclude the successful acquisition of useful tissue. Cancer 2013. © 2012 American Cancer Society.